Reaching for yield and the housing market: Evidence from 18th-century Amsterdam - Korevaar, Matthijs (Journal of Financial Economics, 2023)
Do investors reach for yield when interest rates are low and does this behavior affect the housing market? Using the unique setting and data of 18th-century Amsterdam, I show that reach-for-yield behavior of wealthy investors resulted in a large boom and bust in house prices and major changes in rental yields. Exploiting changes in the supply of bonds, I show that investors living off capital income shifted their portfolios towards real estate and other higher-yielding assets when bond yields were low and decreasing. This behavior exacerbated house price volatility and increased housing wealth inequality.